Homens que fazem sexo com homens: políticas públicas de prevenção às DST/Aids para uma população anônima - Costa, Adriano Henrique Caetano (2011)
The present study aims to analyze the social construction of vulnerability to HIV/Aids of men who have sex with men (MSM) in the city of Fortaleza, approaching the Brazilian politics of HIV/Aids prevention. The speeches of three social protagonists are examined: the national governmental Aids agency (DN DST/Aids and HIV), the Non-Governmental Agency (GRAB), that receives technical and financial support to execute prevention projects with “gay population and others MSM”, including MSM that walk around the city. Three important points of analysis are established: the globalization (and the relations between global and local), the constitution of a community or a social group and the construction of a sexual culture. The methodological strategy of this research involves the collection and analysis of data from different origins, types and qualities. Official documents, scientific publications on identity and HIV/Aids, projects elaborated by GRAB and a field research on MSM are analyzed. This analysis intends to highlight potentialities and limits of identity politics, suggesting the attention to the intersections between sexual orientation, gender identity, race and class, and the intersubjetive contexts established by individuals in their erotic sociabilities. These reflections allow to propose actions for STD/Aids prevention in counterpoint to the identitary speeches in vigor.